Save More Tomorrow™: Using Behavioral Economics to Increase Employee Saving - Thaler, Richard H.; Benartzi, Shlomo (Journal of Political Economy, 2004)
As firms switch from defined-benefit plans to defined-contribution plans, employees bear more responsibility for making decisions about how much to save. The employees who fail to join the plan or who participate at a very low level appear to be saving at less than the predicted life cycle savings rates. Behavioral explanations for this be-havior stress bounded rationality and self-control and suggest that at least some of the low-saving households are making a mistake and would welcome aid in making decisions about their saving. In this paper, we propose such a prescriptive savings program, called Save More Tomorrow (hereafter, the SMarT program). The essence of the program is straightforward: people commit in advance to allocat-ing a portion of their future salary increases toward retirement savings. We report evidence on the first three implementations of the SMarT program. Our key findings, from the first implementation, which has We are grateful to Brian Tarbox for implementing the Save More Tomorrow plan and for sharing the data with us. We would also like to thank many people at the following